Historical and Contemporary Maternal Population Structuring in the Endangered Hastings River Mouse ( Pseudomys oralis ) - Dean R. Jerry; Tanya A. Dow; Martin S. Elphinstone; Peter R. Baverstock (Conservation Biology, 1998)
The Hastings River mouse ( Pseudomys oralis ) is a small, endangered Australian conilurine rodent. Only about 200 specimens of this rodent have ever been caught, and little is known about its biology. At present, populations of this species appear to be severely fragmented. We used temperature‐gradient gel electrophoresis and DNA sequencing to investigate maternal population structuring in this species and to determine if the pattern of fragmentation is the consequence of anthropogenic influences. Based on a 345 bp section of the mitochondrial control region, all sample localities were found to be genetically distinct, with only 1 haplotype out of 11 found present in more than one sample locale. Phylogenetic reconstructions from sequence data clustered haplotypes into two distinct clades, demonstrating that contemporary population structure in the Hastings River mouse has a historical component. The discovery that populations of the Hastings River mouse are not only currently genetically isolated but have been separated for long periods of evolutionary time has clear management ramifications for the conservation of this species. In particular, each population should now be treated as demographically independent and administered as a separate management unit. Estructura Histórica y Contemporánea de la Población Materna de el Ratón del Rio Hastings ( Pseudomys oralis ) en Peligro de Extinción. El ratón del río Hastings ( Pseudomys oralis ) es un roedor australiano pequeño en peligro de extinción. Unicamente 200 especímenes de este roedor han sido capturados y se conoce muy poco de su biologia. Actualmente, las poblaciones de esta especie aparentan estar severamente fragmentadas. Utilizamos gel electroforésis de gradiente de temperatura y secuenciado de ADN para investigar la estructura poblacional materna en la especie y para examinar si los patrones de fragmentación son consecuencia de influencias antropogénicas. Basados en secciones de 345 bp de la region de control mitocondrial, todas las muestras fueron encontradas genéticamente distintas, con un haplotipo de once encontrados presente en mas de una muestra. Reconstrucciones filogenéticas de datos de secuencias agrupó haplotipos en dos grupos distintivos, demostrando que poblaciones contemporáneas del raton del río Hastings tiene un componente histórico. El descubrimiento de que poblaciones del ratón del río Hastings no estan solo aisladas genéticamente en la actualidad, sino que han estado separadas por largos períodos de tiempo evolucionario tiene ramificaciones claras de manejo para la conservación de esta especie. En particular, cada población deberá ser tratada ahora como demográficamente independiente y administrada como una unidad de manejo separada.